On self- and other-regarding cooperation: Kant versus Berge - Unveren, Burak; Donduran, Murat; Barokas, Guy (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2023)
This study analyzes the space of all continuous and discrete games to see whether self-and other-regarding cooperation are similar or inherently different. The solution concept for self-regarding cooperation is the Kantian equilibrium while other-regarding (i.e., altruistic) cooperation corresponds to the Berge equilibrium. We find that any Pareto-efficient Berge is generically a Kantian equilibrium in all symmetric games (e.g., prisoner's dilemma, stag hunt, etc.), whether they are continuous or discrete. In asymmetric games, however, Kant and Berge are generically different. These results suggest that self-and other-regarding cooperation is tight-knit under symmetry, a ubiquitous assumption in applied game theory, albeit asymmetric games do not allow a similar close connection.& COPY; 2023 Elsevier Inc. All rights reserved.
Keywords: Cooperation; Kantian equilibrium; Berge equilibrium; EXISTENCE; NASH; Business & Economics